The Effect Of Employee Empowerment On Innovation Implementation Behavior Moderated By Servant Leadership - HELFITRI, Della Helfitri; Syahrizal, Syahrizal (Universitas Negeri Padang, 2024)
The aim of this research is to research about. (1) the influence of employee employment on the Innovation Implementation Behavior of Bank Nagari employees (2) the influence of servant leadership on the Innovation Implementation Behavior of Bank Nagari employees (3) the influence of employee employment on the Innovation Implementation Behavior of Bank Nagari employees which is moderated by servant leadership. The type of research is quantitative descriptive research, the data source is primary data, and the data collection technique is through distributing questionnaires which are distributed directly to PT Bank Nagari employees. The results of the research are (1) there is a significant influence of employee employment on the Innovation Implementation Behavior of Bank Nagari employees (2) there is a significant influence of servant leadership on the Innovation Implementation Behavior of Bank Nagari employees (3) there is a significant influence of employee employment on the Innovation Implementation Behavior of Bank Nagari employees. moderated by servant leadership.